Фінансовий потенціал-основа економічного управління підприємством - Гаєвська, Лариса Миколаївна; Марченко, Ольга Іванівна; Марченко, Ольга (Приазовський економічний вісник, 2020)
В роботі аргументована важливість фінансового потенціалу, так як вона характеризується як один з основних факторів, від якого залежить ефективне функціонування підприємства. Визначено, що фінансовий потенціал містить в собі певний набір інструментів та різноманітних видів підприємницької діяльності. Різностороння будова складових та характерні особливості функцій економічного потенціалу характеризуються різноманітними підходами до визначення даної концепції. Авторами був зроблений аналіз різних підходів науковців до класифікації потенціалу підприємства, поняття «фінансового потенціалу» та «управління фінансового потенціалу». Охарактеризовано механізм управління фінансовим потенціалом підприємства. Головні аспекти дієвого управління фінансовим потенціалом підприємства були взяті за основу дослідження. Робота основана на ідеях формування концептуальних положень задля ефективного функціонування системи фінансового управління на засадах галузевого рівня. Дослідження теоретичних та методологічних підходів до формування фінансового потенціалу надало можливість обґрунтувати методи аналізу та оцінки загального рівня. Встановлена необхідність утворення дієвої системи управління фінансовими ресурсами для галузі, із врахуванням фінансового, виробничого та ресурсного потенціалу.

The importance of financial potential is argued in the paper as it is characterized as one of the main factors on which the effective functioning of the enterprise depends. It is determined that the financial potential includes a certain set of tools and various types of business activities. The versatile structure of the components and the characteristic features of the economic potential functions are characterized by various approaches to defining this concept. The authors analyzed the different approaches of scientists to the classification of enterprise potential, the concept of "financial potential" and "management of financial potential". The mechanism of management of the financial potential of the enterprise is characterized. The main aspects of the effective management of the financial potential of the enterprise were taken as the basis of the study. The study of theoretical and methodological approaches to the formation of financial potential has made it possible to substantiate methods of analysis and evaluation of the general level. The necessity of establishing an effective system of financial resources management for the industry, taking into account financial, production and resource potential, has been established. The classification of financial potential by functional orientation is proposed as a basis for evaluating the financial potential of business development, which integrates financial security potential, financial flexibility potential, value creation potential. A sequence of assessments of financial capacity of economic entities for financial regulation purposes is disclosed. Scientific and methodological recommendations can be used in carrying out a comprehensive assessment of the financial potential of economic entities by hierarchical levels, which provides the formation of an information base for identifying unused reserves and justifying the choice of financial regulation strategy for the development of economic entities. An integrated assessment of the financial capacity of business entities will allow us to assess the extent to which the financial potential is utilized, to predict its future status and to develop appropriate business development guidance.
Financial potential is the basis of Economic Management of the Enterprise
Keywords: фінансовий потенціал; структура фінансового потенціалу; фінансове регулювання розвитку суб’єктів господарювання; капітал; управління фінансовим потенціалом; фінансові ресурси; financial potential; structure of financial potential; financial regulation of the development of business entities; capital; financial capacity management; financial resources